1997
DOI: 10.1359/jbmr.1997.12.9.1396
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Aldehyde Inhibitors of Cathepsin K Inhibit Bone Resorption Both In Vitro and In Vivo

Abstract: We have shown previously that cathepsin K, a recently identified member of the papain superfamily of cysteine proteases, is expressed selectively in osteoclasts and is the predominant cysteine protease in these cells. Based upon its abundant cell type-selective expression, potent endoprotease activity at low pH and cellular localization at the bone interface, cathepsin K has been proposed to play a specialized role in osteoclast-mediated bone resorption. In this study, we evaluated a series of peptide aldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(102 citation statements)
references
References 39 publications
3
98
0
1
Order By: Relevance
“…In fact, in vitro and in vivo studies suggest that the 2 types of proteases, MMP-9 and cathepsin K, are involved in bone resorption mediated by osteoclasts, performing the collagen degradation in bone (Delaisse et al, 2003;Everts et al, 1992). Votta et al (1997) found reduced bone resorption, both in vitro and in vivo, using an inhibitor of cathepsin K. Moreover, cathepsin K-deficient mice showed significant osteopetrosis (Saftig et al, 1998;Gowen et al, 1999). In periodontal area, increased levels of cathepsin K Figure 4.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, in vitro and in vivo studies suggest that the 2 types of proteases, MMP-9 and cathepsin K, are involved in bone resorption mediated by osteoclasts, performing the collagen degradation in bone (Delaisse et al, 2003;Everts et al, 1992). Votta et al (1997) found reduced bone resorption, both in vitro and in vivo, using an inhibitor of cathepsin K. Moreover, cathepsin K-deficient mice showed significant osteopetrosis (Saftig et al, 1998;Gowen et al, 1999). In periodontal area, increased levels of cathepsin K Figure 4.…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition of Cathepsin K activity was assessed using a fluorimetric assay as previously described (20). Z-Phe-Arg-AMC (Z-Phe-Arg 7-amido-4-methylcoumarin hydrochloride, SIGMA, France) at 10 µM was used as cathepsin K substrate.…”
Section: -6 Cathespin K Inhibitionmentioning
confidence: 99%
“…In contrast, leupeptin, chymostatin, and E-64-d showed no appreciable inhibition toward fertilization at 100 mM. Although MG-132 can also inhibit cysteine protease activity, 17) the effect of MG-132 appears to be on the proteasome, since E-64-d (a potent cysteine-protease inhibitor) showed no inhibition toward fertilization (Fig. 1).…”
Section: Effects Of Protease Inhibitors On Fertilizationmentioning
confidence: 95%